2011
DOI: 10.1097/acm.0b013e31820469d6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Supply of Rural Family Physicians: Recent Outcomes From Jefferson Medical Collegeʼs Physician Shortage Area Program (PSAP)

Abstract: Despite major changes in health care in recent decades, Jefferson's PSAP continues to represent a successful model for substantially increasing the supply and distribution of rural family physicians. Especially with the forthcoming expansion in health insurance, access to care for rural residents will require an increased supply of providers. These results may also be important for medical schools planning to develop similar rural programs, given the new Rural Physician Training Grants program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 14 publications
2
84
0
3
Order By: Relevance
“…Of 21 different programs (described in 26 papers), 15 were primary care courses added to the conventional curriculum. [49][50][51][52][53][55][56][57][58][59][63][64][65][66][68][69][70][71][72] The remaining six programs were special curricula or medical schools focusing on primary care and/or rural health. 47,48,54,[60][61][62] , Contrary to the studies on clerkships, the most frequently studied outcomes of longitudinal programs were career choices after graduation (n=15).…”
Section: Impact Of Interventions On Primary Care Specialty Choicementioning
confidence: 99%
See 2 more Smart Citations
“…Of 21 different programs (described in 26 papers), 15 were primary care courses added to the conventional curriculum. [49][50][51][52][53][55][56][57][58][59][63][64][65][66][68][69][70][71][72] The remaining six programs were special curricula or medical schools focusing on primary care and/or rural health. 47,48,54,[60][61][62] , Contrary to the studies on clerkships, the most frequently studied outcomes of longitudinal programs were career choices after graduation (n=15).…”
Section: Impact Of Interventions On Primary Care Specialty Choicementioning
confidence: 99%
“…With one exception, 72 all high quality studies were from the United States, and most of them had a positive impact (Table 3). Components of these programs included longitudinal preclinical preceptorships, 47,49,50 family medicine faculty advisors, 52 clinical rotations at rural or regional sites, 47,48,50,52,54 workshops or seminars on primary care, [48][49][50] and community-based projects. 50 Most of them also recruited students according to predictors of career choice previously described in the literature, including the students' childhood community and interest in primary care.…”
Section: Impact Of Interventions On Primary Care Specialty Choicementioning
confidence: 99%
See 1 more Smart Citation
“…As part of our ongoing longitudinal study of PSAP graduates, 19,20,23,25 2007), which maintains an address dataset of JMC alumni that is updated every 3 months and has been found to be highly accurate. 19 As in prior studies, office address (county) was used, 19,20,23,25 and when it was unavailable we used home address county, assuming it was of similar rurality.…”
Section: Methodsmentioning
confidence: 99%
“…22 Outcomes of the first 25 JMC graduating classes (1978 -2002) showed that PSAP graduates were significantly more likely to practice rural family medicine than their peers and that their longterm rural family medicine retention rate after 11 to 16 years was 79%. [23][24][25] Because of the critical need to identify ways to increase the supply of rural women physicians, this study looked at the specific outcomes of the PSAP for women. It focused on graduates of more recent years (1992)(1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002) to better reflect the current female composition in medical schools.…”
Section: -Council On Graduate Medical Education10th Reportmentioning
confidence: 99%